Style Individualization in the Ukrainian Translations of Fr. Jan Twardowski’s Poems (Case Study of the Book of Poems “We must go on …”) (Linguostylistic Studies, 2020)
The article considers the stylistic features of Fr. J. Twardowski’s poetic works and their equivalents in the Ukrainian translations. The case study of the issue is the bilingual poetic volume of  We must go on or a ladybug walk translated by T. Chernysh and S. Yermolenko. The issue of the value identity, present in the original and translations, is argued by determining the typological and individual features of translation transformations. The author analyzes the ways of using translation constructions, indicating the level of assimilating figurative language of the original poems in Ukrainian versions, with a focus on the metaphorization of life and nature, syntactic and punctuation specifics of the poems by Fr. J. Twardowsk. The study argues that a form of vers libre provides translators with new opportunities for transmitting the author’s symbols to the Ukrainian reader. The preservation of the inner rhythm of the poems, their melody, thoughtful structure, which is associated with the phenomenon of the concept of “image” have been emphasized.The concept of “image” has become the starting point in the analysis of individual and typological lexical items and common semantic expressions. The compliance analysis (translation equivalence) allows better understanding of the original structures and facilitates the general vision of the reproduction correctness of the original communicative intentions in the translation. In addition, the work combines linguistic and stylistic approach with a general interpretive and cultural method, which allows identifying the individual style of the author and the degree of translator’s adaptation of them to the Ukrainian realities.The key findings of the study manifest that the author’s most favored stylistic means and devices are: anaphora, obvious and hidden antonymy, metaphorical expressions, conveying the Polish realities in which he lived and worked, religious symbols, emotionality of the colloquial vocabulary, and dialogism of the style. The conclusion is that Twardowski’s poems in the book of poems “We must go on…” are translated into Ukrainian at a high professional level, there are many individual findings, although it is not the only possible way to reveal the author’s style. It is advisable to analyze stylistic features of the whole complex of Twardowski poetry translations into Ukrainian in future researches.
Keywords: translation transformations,; writing style,; method of comparative translation analysis,; stylistic features,; untranslatability.